2021
DOI: 10.3390/su13105745
|View full text |Cite
|
Sign up to set email alerts
|

Livestock and Small-Scale Irrigation Scheme Interactions as a Key Source for Sedimentation during the Irrigation Season: Four Case Studies from South-West Shoa, Ethiopia

Abstract: Small-scale irrigation (SSI) development can play a major role in Ethiopia’s economic development, but sedimentation is a major threat to its sustainability. The focus of the dominant discourse around the sedimentation of SSI schemes lies in upstream catchment protection during the rainy season, neglecting both protection against erosion through overland flow along the margins of the canal network and sedimentation caused by livestock disturbances. Remedies against the latter causes of sedimentation during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This was attributed to the effect of the reduction in surface roughness in the trampled areas, promoting greater connectivity and more frequent flow (Greenwood & Meusburger, 2019). In Ethiopia, the identification of sources and the extent of sedimentation in small‐scale irrigation schemes, staggered with livestock activity, showed that channel sedimentation occurs through disturbances caused by cattle encroaching on the river banks to graze and drink water (Dessalegn et al, 2021). The results of this study corroborate our results for the watersheds with channel disturbances by cattle movement, and these channels flow into the Passo Real reservoir, which may increase its sedimentation.…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to the effect of the reduction in surface roughness in the trampled areas, promoting greater connectivity and more frequent flow (Greenwood & Meusburger, 2019). In Ethiopia, the identification of sources and the extent of sedimentation in small‐scale irrigation schemes, staggered with livestock activity, showed that channel sedimentation occurs through disturbances caused by cattle encroaching on the river banks to graze and drink water (Dessalegn et al, 2021). The results of this study corroborate our results for the watersheds with channel disturbances by cattle movement, and these channels flow into the Passo Real reservoir, which may increase its sedimentation.…”
Section: Discussionmentioning
confidence: 99%